Cost of a measles outbreak in a remote island economy: 2014 Federated States of Micronesia measles outbreak. Issue 43 (13th October 2017) - Pike, Jamison; Tippins, Ashley; Nyaku, Mawuli; Eckert, Maribeth; Helgenberger, Louisa; Underwood, J. Michael
Highlights: We assessed the economic burden of the 2014 Federated States of Micronesia (FSM) measles outbreak, taking into account their unique challenges in confirming diagnosis and containing the outbreak. Under the Compact of Free Association, FSM receives immunization funding and technical support from the United States domestic vaccination program managed by the Centers for Disease Control and Prevention. Although the US paid the majority of total costs of the outbreak, examining each country's costs relative to their respective economy illustrates a far greater burden to FSM. Abstract: After 20 years with no reported measles cases, on May 15, 2014 the Centers for Disease Control and Prevention (CDC) was notified of two cases testing positive for measles-specific immunoglobulin M (IgM) antibodies in the Federated States of Micronesia (FSM). Under the Compact of Free Association, FSM receives immunization funding and technical support from the United States (US) domestic vaccination program managed by the Centers for Disease Control and Prevention (CDC). In a collaborative effort, public health officials and volunteers from FSM and the US government worked to respond and contain the measles outbreak through an emergency mass vaccination campaign, contact tracing, and other outbreak investigation activities. Contributions were also made by United Nations Children's Emergency Fund (UNICEF) and World Health Organization (WHO). Total costs incurred as a result of the outbreak were nearly 4, 000, 000; approximately 10, 000 per case. Direct medical costs (≈141, 000) were incurred in the treatment of those individuals infected, as well as lost productivity of the infected and informal caregivers (≈250, 000) and costs to contain the outbreak (≈3.5 million). We assessed the economic burden of the 2014 measles outbreak to FSM, as well as the economic responsibilities of the US. Although the US paid the majority of total costs of the outbreak (≈67%), examining each country's costs relative to their respective economy illustrates a far greater burden to FSM. We demonstrate that while FSM was heavily assisted by the US in responding to the 2014 Measles Outbreak, the outbreak significantly impacted their economy. FSM's economic burden from the outbreak is approximately equivalent to their entire 2016 Fiscal Year budget dedicated to education.